Securitization as a response to monetary policy - Zhang, Jiarui; Xu, Xiaonian (John Wiley & Sons Ltd, 2019)
This paper studies how monetary easing provides incentives for banks to take risk and issue mortgage‐backed securities (MBS) and, because MBS have the “lemon” property, why MBS buyers are willing to purchase high‐risk securities at high prices. Banks need equity to attract deposits. Monetary easing reduces this need, and banks leverage up and reduce their monitoring efforts. The internal need for liquidity and risk sharing motivates banks to issue MBS. Security buyers understand the moral hazard problem that banks face but are willing to purchase bank securities at high prices because monetary easing would also reduce their cost of funds.